Portugal’s leftist government: from sick man to poster boy? - Fernandes, J. M. A.; Magalhães, P.; Santana Pereira, J. (South European Society and Politics, 2018)
In 2015, for the first time in the history of Portuguese democracy, radical left parties relinquished their status as outsiders and lent their support to a Socialist Party cabinet. Defying the expectations of many, this government survived its first years. In fact, it did more than survive: while largely fulfilling the interparty agreements that originated it, the government has presided over positive economic developments and even managed to abide by EU budgetary rules. How was this possible? We show that the political solution found, as well as the policies and practices that sustain it, involve a form of a ‘contract parliamentarism’. This solution has allowed the parties to the left of the Socialists to obtain policy benefits without compromising their core identity or significantly hindering the support of their constituents.